Assessment for distinctiveness: recognising diversity of accomplishments. Issue 7 (3rd July 2021) - Jorre de St Jorre, Trina; Boud, David; Johnson, Elizabeth D.
ABSTRACT: Universities have responded to the expansion of higher education and restructuring of the labour market by redesigning curriculum to better emphasise transferable skills and embed pedagogies that contribute to graduate employability. However, the ways in which universities judge and share achievement still provides poor evidence of what students can do or the skills and personal attributes that inform job recruitment decisions. Furthermore, assessment provides little opportunity for students to develop the self-knowledge or evaluative judgement needed to portray their professional identity to different audiences. In this paper, we examine shortcomings of current approaches to assessment and propose four principles for redesign of 'assessment for distinctiveness' that recognises students' unique and complex achievements in ways that are relevant to employers, and enable students to understand and appropriately portray their achievements for different audiences.